Exploring the great outdoors - Mayer, Mercer, 1943- (New York, NY : Harper, an imprint of HarperCollins Publishers, 2019)
Little Critter and his classmates take a field trip into the woods to study their natural surroundings. They see little bugs, big trees, and lots of animal tracks. There's so much to see and do and explore! Little Critter discovers that there are plenty of surprises in store when it comes to the great outdoors.
"My first I can read book"--Spine.
Guided reading level H.
Keywords: Little Critter -- (Fictitious character) -- Juvenile fiction; Hiking -- Juvenile fiction; Readers (Elementary); Children's stories; Readers (Publications)